2006
DOI: 10.1086/506254
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Observations of the Anomalous Microwave Emission in the Perseus Molecular Complex with the COSMOSOMAS Experiment

Abstract: The anomalous microwave emission detected in the Perseus molecular complex by Watson et al. has been observed at 11 GHz through dual orthogonal polarizations with the COSMOSOMAS experiment. Stokes U and Q maps were obtained at a resolution of ∼ 0 • .9 for a 30 • ×30 • region including the Perseus molecular complex. A faint polarized emission has been measured; we find Q = −0.2% ± 1.0%, while U = −3.4 +1.8 −1.4 % both at the 95% confidence level with a systematic uncertainty estimated to be lower than 1% determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 33 publications
10
62
1
Order By: Relevance
“…For the size distribution used to account for the PAH emission features in the infrared results, the predicted rotational emission appears to be in agreement with the observed intensity of dust-correlated microwave emission (e.g., Dobler et al 2009;). There do not appear to be any mechanisms that can effectively align PAH angular momenta with the galactic magnetic field (Lazarian & Draine 2000), and the rotational emission from PAHs is therefore expected to be essentially unpolarized, in agreement with upper limits on the polarization of the dust-correlated microwave emission (Battistelli et al 2006;Mason et al 2009). By contrast, the far-infrared and submm emission from larger grains is expected to have polarizations as large as ∼10% (Draine & Fraisse 2009) -soon to be measured by Planck.…”
Section: Modeling the Ir Emissionsupporting
confidence: 59%
“…For the size distribution used to account for the PAH emission features in the infrared results, the predicted rotational emission appears to be in agreement with the observed intensity of dust-correlated microwave emission (e.g., Dobler et al 2009;). There do not appear to be any mechanisms that can effectively align PAH angular momenta with the galactic magnetic field (Lazarian & Draine 2000), and the rotational emission from PAHs is therefore expected to be essentially unpolarized, in agreement with upper limits on the polarization of the dust-correlated microwave emission (Battistelli et al 2006;Mason et al 2009). By contrast, the far-infrared and submm emission from larger grains is expected to have polarizations as large as ∼10% (Draine & Fraisse 2009) -soon to be measured by Planck.…”
Section: Modeling the Ir Emissionsupporting
confidence: 59%
“…The best constraint comes from the Perseus region, which has significant AME emission and relatively little contaminating synchrotron emission. Battistelli et al (2006) reported a weak detection in Perseus at 3.4 +1.5 −1.9 % at 11 GHz, while later measurements obtained by López-Caraballo et al (2011) using WMAP data found a 2σ limit of <1%; Dickinson et al (2011) have also measured a 2σ limit of <1.4% for Perseus (as well as an upper limit of <1.7% in ρ Ophiuchus), and Génova- Santos et al (2015) found a 2σ limit of <2.8% in Perseus at 19 GHz. Recently, Battistelli et al (2015) have claimed to detect polarized AME emission at 21.5 GHz from RCW 175, an H ii region, where they measured a polarization percentage of (2.2 ± 0.2 (random) ± 0.3 (systematic))% at 21.5 GHz.…”
Section: Limits On Ame Polarizationmentioning
confidence: 90%
“…Spinning dust emission is observed to be at most weakly polarised, of order a few percent (Battistelli et al 2006;López-Caraballo et al 2011;Dickinson et al 2011). On the theoretical side, Lazarian & Draine (2000) predict very low (but possibly measurable) levels of polarisation for spinning dust emission.…”
Section: Polarisation Of Other Ism Emissionmentioning
confidence: 99%